Design and Creation of Book Inventory Management System in School Library - Mardiyati, Sri; Pauziah, Ulfa; Sutrisno, Danang (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The implementation of a digital book inventory system in school libraries plays a critical role in enhancing the efficiency, accuracy, and reliability of collection management. Traditional manual systems often result in challenges such as data redundancy, misplaced records, delayed reporting, and a higher risk of human error, all of which can disrupt library operations and hinder effective information access. In response to these challenges, this study was conducted to design and develop a web-based book inventory management system tailored specifically for school library needs. The system aims to automate core processes including book cataloging, borrowing and returning transactions, and inventory reporting. The development methodology adopted is the Waterfall model, a structured approach that includes sequential stages: requirement analysis, system design, implementation, testing, deployment, and maintenance. To support detailed system modeling, Unified Modeling Language (UML) tools were utilized, ensuring a comprehensive blueprint of system functionalities and data flow. The findings of the study indicate that the implementation of the system significantly reduces administrative workload, improves the accuracy of inventory records, and provides real-time data access to library administrators. Moreover, the system enhances the overall user experience by offering a more organized, accessible, and transparent library service. This innovation serves as a foundation for future enhancements such as mobile access or integration with online academic platforms.